Non-communicable Diseases and Cognitive Impairment: Pathways and Shared Behavioral Risk Factors Among Older Chinese - Yiengprugsawan, Vasoontara Sbirakos; Browning, Colette Joy (Frontiers in Public Health, 2019)
Population aging has brought about a number of challenges to public health and primary health care systems due to increases in the prevalence of non-communicable diseases (NCDs). As a country with one of the largest populations globally, China is confronting a rising number of chronic NCDs including cardiometabolic related conditions. This mini-review investigates the link between NCDs and cognitive impairment through common risk factors. Identifying risk factors is important for the prevention and management of these chronic conditions. In addition, this review also identifies the role of primary health care services in reducing behavioral risk factors for NCDs and cognitive impairment. Addressing shared determinants and pathways is important in the design of public health interventions and primary health care services in China. Monitoring and management of NCD biomarkers and behavioral risk factors may also be beneficial for cognitive health among older Chinese.